Classification of respiratory diseases and COVID-19 from respiratory and cough sound using deep learning techniques - Ahasan, Md. Mubtasim; Fahim, Mohammad; Mazumder, Himadri; Fatema, Nur E; Rahman, Sheikh Mustafizur (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.